Multi-Anttmonopole Soluttons Of The SU(2) Yang-Mtlls-Higgs Field Theory. - Teh, Rosy, Chooi Gim; Wong, Khai-Ming (2008)
We report on the existence of multi-antimonopole soluttions of the SU(2) Yang-Mills-Higgs field theory.